Burden of non-communicable diseases in Cyprus, 1990-2017: findings from the Global Burden of Disease 2017 study - Charalampous, Periklis; Pallari, Elena; Tyrovolas, Stefanos; Middleton, Nicos; Economou, Mary; Devleesschauwer, Brecht; Haagsma, Juanita A. (My University, 2021)
Non-communicable diseases (NCDs) accounted for over 90% of all deaths in the Cypriot population, in 2018. However, a detailed and comprehensive overview of the impact of NCDs on population health of Cyprus over the period of 1990 to 2017, expressed in disability-adjusted life years (DALYs), is currently not available. Knowledge about the drivers of changes in NCD DALYs over time is paramount to identify priorities for the prevention of NCDs in Cyprus and guide evidence-based decision making. The objectives of this paper were to: 1) assess the burden of NCDs in terms of years of life lost (YLLs), years lived with disability (YLDs), and DALYs in Cyprus in 2017, and 2) identify changes in the burden of NCDs in Cyprus over the 28-year period and assess the main drivers of these changes.
Keywords: Burden of disease; Cyprus; Non-communicable diseases